ACCELERATING OIL PALM SMALLHOLDER PLANTATION REJUVENATION PROGRAM TO MAINTAIN SUSTAINABLE SUPPLY OF PALM OIL (International Seven Journal of Multidisciplinary, 2025)
Indonesia’s dominance in the global palm oil market increasingly depends on the productivity and sustainability of smallholder plantations, which currently face declining yields due to aging crops, poor seed quality, and limited access to institutional support. In response to this critical issue, this study aims to analyze the structural and policy-related barriers to accelerating smallholder oil palm plantation rejuvenation and explore scalable solutions to maintain a sustainable supply of palm oil. Employing a qualitative literature review method, the research systematically examines secondary sources published between 2015 and 2025, including peer-reviewed journal articles, government policy documents, and institutional reports. Data collection was conducted through purposive selection from academic databases, and all sources were managed using Mendeley Desktop. The data were analyzed using thematic content analysis to extract recurring patterns related to governance, finance, land legality, seed quality, and technical support. The findings reveal that high replanting costs, limited access to credit, complex administrative procedures, and widespread land tenure insecurity are the main constraints hindering smallholder rejuvenation. In contrast, bundled interventions integrating land certification, financial assistance, technical extension, and digital tools show strong potential for scaling. This study concludes that a coordinated, inclusive, and well-financed policy framework is essential to transform replanting initiatives into a driver of national supply resilience. Future research is recommended to evaluate region-specific implementation models and measure the long-term impacts of policy interventions at the community level.